Dynamics and variegation in the Treg response to Interleukin-2 - Kumba Seddu; Kaitavjeet Chowdhary; Molly Henderson; Jakub Tomala; Odhran Casey; Yi Cao; Diane Mathis; Jamie B. Spangler; Christophe Benoist (Proceedings of the National Academy of Sciences, 2025)
Interleukin-2 (IL2) is the key trophic factor for T regulatory (Treg) cells, controlling their differentiation and homeostasis. To understand how temporally regulated responses to IL2 unfold in Tregs, we performed fine time-course analyses, at population and single-cell levels, of changes in chromatin architecture and mRNAs induced by IL2 in Tregs in vivo. The data revealed responses that were largely uniform in rTreg, but diverse among aTregs, matching different STAT5 signal transduction efficiency. Individual Tregs displayed divergences in the preponderance of changes that may be attributed to STAT1 or STAT5 signal transduction downstream of IL2. Chromatin analysis identified an evolving implication of transcription factors that accounted for the waves of responsive genes. Covalent cytokine/Ab complexes that preferentially trigger high- (heterotrimer) or low-affinity (heterodimer) IL2 receptors activated the same signatures, yet with strong quantitative variations, especially in NK cells. Thus, IL2 is not a monolithic activator for Tregs, but a variegated sculptor of Treg identity.